2013
DOI: 10.1002/pola.26576
|View full text |Cite
|
Sign up to set email alerts
|

Poly(methyl methacrylate‐co‐pentaerythritol tetraacrylate‐co‐butyl methacrylate)‐g‐polystyrene: Synthesis and high oil‐absorption property

Abstract: Well-defined high oil-absorption resin was successfully prepared via living radical polymerization on surface of polystyrene resin-supported N-chlorosulfonamide group utilizing methyl methacrylate and butyl methacrylate as monomers, ferric trichloride/iminodiacetic acid (FeCl 3 /IDA) as catalyst system, pentaerythritol tetraacrylate as crosslinker, and L-ascorbic acid as reducing agent. The polymerization proceeded in a ''living'' polymerization manner as indicated by linearity kinetic plot of the polymerizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Polymeric gels are crosslinked polymers that can absorb large amount of polar or non‐polar solvents depending on their chemical structure, that is, hydrophobic polymeric gels absorb organic solvents and oils while hydrophilic polymeric gels have very high water absorption properties. A great number of organic solvent and oil absorbent polymeric gels have been reported in literature . However, new organic solvent absorbents with high absorption capacity, low water pickup and reusability are still required.…”
Section: Introductionmentioning
confidence: 99%
“…Polymeric gels are crosslinked polymers that can absorb large amount of polar or non‐polar solvents depending on their chemical structure, that is, hydrophobic polymeric gels absorb organic solvents and oils while hydrophilic polymeric gels have very high water absorption properties. A great number of organic solvent and oil absorbent polymeric gels have been reported in literature . However, new organic solvent absorbents with high absorption capacity, low water pickup and reusability are still required.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the contact angle 43 (the angle formed by the intersection of the oil-water interface) gives a better idea about the wettability of the sorption surface. Small contact angles (80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90) correspond to high wettability, when the liquid spreads on the surface. Similarly, large contact angles (140)(141)(142)(143)(144)(145)(146)(147)(148)(149)(150) correspond to low wettability, when the liquid beads on the surface.…”
Section: Principles Of Oil In Water Separationmentioning
confidence: 99%
“…A novel octadecyl acrylate (OA)/acrylic acid copolymer on the surface of polyethylene terephthalate (PET), which is considered to be a non‐woven fiber, is also effective for the treatment of oil spills 88 . Chen et al 89 reported a novel polymer resin namely poly(methyl methacrylate–co‐pentaerythritol tetraacrylate‐co‐butyl methacrylate)‐ g ‐polystyrene for oil sorption by living radical polymerization on the surface of PS resin using ferric trichloride/iminodiacetic acid as a catalyst. The oil sorption behavior of polymer was tested using toluene as the solvent.…”
Section: Organic Polymer Nanocomposite Sorbentsmentioning
confidence: 99%
“… 46 Trimethylolpropane triacrylate (TMP-3A), pentaerythritol tetraacrylate (PET-4A), and bis-pentaerythritol hexaacrylate (PET-6A) are well-known polymer cross-linkers used in several industrial applications that can give branched polymers at the correct monomer:cross-linker ratio ( Figure 3 ). 47 , 48 However, to the best of our knowledge, these cross-linkers have not been used to make branched KHI polymers. Here, we report the first study of branched versus linear PVCap using these three cross-linkers to form polymers with essentially 3, 4, and 6 branches.…”
Section: Introductionmentioning
confidence: 99%